Creating sustainable children's clothing designs using reversed clothing, inspired by Sadu motifs, to support the tourism sector in the Kingdom of Saudi Arabia (Al-Academy, 2025)
Children's fashion design is one of the applied visual arts that represents the core and backbone of the ready-to-wear clothing industry, as it depends on the child's ability to meet his health, psychological and social needs through his clothing. The Kingdom of Saudi Arabia is rich in cultural heritage and historical legacy that confirms its role in human civilization, as many civilizations have intersected on its land, and the various heritage sources are considered the distinguishing feature of each people and nation from others. Sadu weaving is a popular art form in the Kingdom of Saudi Arabia, famous for its ancient traditions and distinctive patterns that reflect Saudi culture and heritage. It is an important part of the Kingdom's cultural and artistic heritage. Reversible clothing is a type of transformable clothing, the basic idea of which is that it can be worn on both sides, with each side featuring a different design or fabric in a different color or pattern. The research aims to :1. Create sustainable children's clothing designs using reversed clothing, inspired by Sadu motifs, to support the tourism sector in the Kingdom of Saudi Arabia.2. Determine the level of acceptance by specialists of sustainable children's clothing designs using reversed clothing, inspired by Sadu motifs, to support the tourism sector in the Kingdom of Saudi Arabia.3- Determining the degree of consumer acceptance of sustainable children’s clothing designs in the style of reverse clothing inspired by Sadu motifs to support the tourism sector in the Kingdom of Saudi Arabia. The research recommended :1. Incorporating sustainable design methods into fashion design curricula, with a focus on reversible clothing as an innovative solution that contributes to reducing waste and achieving clothing sustainability.2. Supporting applied research inspired by Saudi heritage that links fashion design with supporting the tourism sector.3- Establishing cooperation agreements between specialized colleges and tourism entities to design innovative, expressive clothing for children visiting tourist areas that combines functional, aesthetic, and cultural design.4- Encouraging local designers to adopt the concept of inverted transformative clothing inspired by local cultural heritage.